Study of Leachability characteristics of fly ash and its effect on soil and ground water contamination - Sweta Bhardwaj (Environment Conservation Journal, 2006)
In the present study  the  leachability  characteristics  of  fly  ash and  its  effect on  soil and  ground  water  contamination. During the course of study it was found that despite the presence of the only trace amount of heavy metal in coal and coal ash, these material have the potential to accumulate in soil  and  increase  in  concentration  by  food  chain biomagnification.